Econazole depleted calcium release-activated calcium (CRAC) current through blockade of voltage-dependent Ca 2+ channels - Agung Endro Nugroho; Hari Purnomo; Kazutaka Maeyama (Indonesian Journal of Pharmacy, 2011)
Econazole  is  an  azole  antifungal  agent  which  can  block  the  calcium release-activated  calcium  (CRAC)  current  in  human  leukaemic  T  cell  line.  The phenomenon  is  also  possible  to  occur  in  mast  cell  such  as  RBL-2H3  (rat basophilic  leukemia)  cells,  a  tumor  analog  of  mast  cells.  In  the  study,  we investigated  effect  of  econazole  on 45Ca2+ uptake  into  the  cells  in  response  to thapsigargin, an ATP-dependent Ca2+ (SERCA) inhibitor, by direct measurement of  radiolabelled  Ca2+ uptake  in  cells.  The  mechanism  underlying  this  effect  of econazole  was  studied  using  molecular  modelling.  In present  study,  econazole inhibited 45Ca2+ influx  into  mast  cells  in  absence  of  mast  cells  inducer, thapsigargin.  Moreover,  econazole  potently  suppressed  the 45Ca2+ influx induced  by  thapsigargin.  It  was  supported  that  econazole  also  inhibited  Ca2+-induced  tracheal  contraction.  The  increase  of  Ca2+ was  stimulated  by  the opening of voltage-dependent Ca2+ channels activated by KCl-induced membrane depolarization. Based on molecular docking study, score of interaction (equal to  energy  of  interaction)  of  3FGO,  a  main  protein  target  on  Ca2+ -ATPase,  with native ligan, thapsigargin and econazole were -76.941, -117.205, and -92.277, respectively.  The  interaction  of  thapsigargin  and  Ca2+ -ATPase  was  more  stable than  this  of  econazole  and  Ca2+ -ATPase.   It  suggests  that  it  would  be  difficult for  econazole  to  block  the  interaction  of  thapsigargin  with  Ca2+ -ATPase  to increase  intracellular  Ca2+.In  conclusion,  econazole  inhibited  the  increase  of intracellular Ca2+involving the blokade of voltage-dependent Ca2+ channels, but not involving the Ca2+ -ATPase pathway.Key words :econazole, Ca2+ -ATPase, CRAC current, thapsigargin